A Distinctive Approach on Safe Driving through Interactive and Behavioral Analysis - Kumar, Kukatlapalli Pradeep; Suraj, Thandassery Sugathan; Pandya, Vandana Lalit; Joseph, Abin (International Journal of Computer Sciences and Engineering, 2019)
As the automobile industry is growing rapidly, every individual has an urge to own the luxurious cars either for comfort or the number of safety features it may provide say the Advanced Driver Assistance System. However, due to the devices, sensors and monitoring systems, it includes such safety features limited to the higher classes of the society. But, safe driving is a requirement for the society as a whole in a holistic understanding. With the growing need for transportation, the life style of human race has transformed a lot. People focus on reaching their destination in minimal time ignoring the safety measures in many instances. This paper elucidates about a mobile application which helps the user in safe driving on different parameters by using smartphone sensors like the Accelerometer and its related technology.